Assessment of plant height and trunk diameter of oil palm as a sole function of soil textural grains (sand, silt and clay) - Teh, Christopher Boon Sung; Sani, Idris; Zaibon, Syaharudin; Sim, Choon Cheak (Malaysian Society of Soil Science, 2024)
Plant height is a key indicator of healthy growth. Given the role of soil texture in productivity, the effects of sand, silt, and clay on the height and diameter of oil palm (OP) were investigated. In the four OP plantations, measurements of total and trunk heights and trunk diameters were taken fromtwo OP clusters: tall and short. A Pro II Laser Rangefinder (ML921) was used to measure heights. Soil samples were subjected to particle distribution analysis using the pipette method. The data were processed using RStudio software. The t-test confirmed a significant difference in the heights between the clusters in all plantations, implying the accuracy of clustering. For total height, the tall cluster was greater than the short by 24.75%, 23.89%, 27.17%, and 27.51% in OP1, OP2, OP3, and OP4, respectively. Regression analysis established that soil texture accounted for 65.3%, 46.8%, 74.4%, and 69.6% of the total OP height in the fields, respectively. Sand showed a strong to moderate positive correlation with total and trunk heights, and a moderate negative correlation with trunk diameter. The clay correlated inconsistently with trunk diameter, while silt in the 0–30 cm layer showed a strong to moderate negative correlation with height. In conclusion, soil texture profoundly influences oil palm height, with sand grains exerting the greatest positive effect. Typical clay soil should be avoided during oil palm site selection, and the fields should be well-leveled to avoid erosion, which results in continuous clay deposition on the bottom slope.